PENGARUH KEBIASAAN MEROKOK TERHADAP KEEFEKTIFAN JALAN NAPAS PADA PASIEN TB PARU - Sri Dewi Br Siregar; Suherni; Yuni Ramadhani; Julidia Safitri Parinduri; Helfrida Situmorang; Hendry Kiswanto Mendrofa (Universitas Pahlawan Tuanku Tambusai, 2022)
Smoking has a 3.8 times the risk of the incidence of tuberculosis. The prevalence of smokers in Indonesia since 2013 has been increasing from year to year, ranking third after China and India with the highest cigarette consumption in the world. Airway ineffectiveness is influenced by the state of the lung health system, this needs to be anticipated and handled properly so that respiratory emergencies do not occur. The purpose of this study was to determine the effect of smoking habits on airway effectiveness. This type of research is a quantitative research using a correlation design with a cross-sectional observation approach. The population in this study was tuberculosis patients. The type of sampling used in this study is non-probability sampling with a total sampling technique of 37 people. Data analysis used a non-parametric correlation statistic test, namely the Spearman correlation test with the assumption that the p vap-value05 to determine the influence between the two variables. Based on the results of the Spearman Correlation test, a p-value of 0.001 was obtained where the p-value < 0.05. This result indicates that there is a significant influence between smoking habits and the effectiveness of the airway in tuberculosis patients, the r-value of 0.589 which indicates that the strength of the relationship between the two variables is in the moderate category. It is suggested to Puskesmas respondents to always provide education about the dangers of smoking behavior in pulmonary TB patients. Keywords: Smoking behavior, pulmonary tuberculosis, airway effectiveness